Performing the "Tribe"? Ethnic Heritage Associations and the UNESCO 2003 Convention in Malawi - Lusaka, Mwayi (African historical review, 2024)
This article explores two interlinked forms of identity expression and heritage production in postcolonial Malawi. The first is the way ethnic communities reconstruct their cultural heritage and identities through the establishment of ethnic-based heritage associations which exhibit heritage at cultural festivals. This points to the shift in cultural production from one that was dictated by the discourse of national culture and single identity to one that is defined by the discourse of heritage which appeals to democratic sensibilities. The second is the inventorying and listing of cultural elements as dictated by the UNESCO 2003 Convention for the Safeguarding of the Intangible Cultural Heritage. It is noted that the proliferation of ethnic-based heritage associations found resonance and synergy with UNESCO's appeals for safeguarding intangible cultural heritage as propagated by its 2003 Convention. However, as the article demonstrates, the imperatives of democracy and the UNESCO 2003 Convention promote ethnic consciousness at the expense of national consciousness. This creates a dilemma in imagining the nation. Drawing on archival and oral evidence, the article argues that the ethnic-based heritage associations, while promoting cultural preservation in line with the UNESCO Convention of 2003, have become sites of political mobilisation where notions of tribe and tribalism are reproduced and reaffirmed. Ultimately, the UNESCO 2003 Convention, while promoting the safeguarding of intangible cultural heritage, reinforces the idea of tribe in Malawi. The article contributes to our understanding of the politics of identity and heritage production in postcolonial Malawi.